Studi Keislaman Di Era Digital: Mengintegrasikan Teknologi Modern Dan Ilmu Pengetahuan Tradisional di SMK Khozinatul Ulum Todanan Blora - Solikin; Muhammad Abu Kholil (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to examine how modern technology integrates with traditional knowledge in teaching Islamic studies at SMK Khozinatul Ulum Todanan Blora. The main focus of this study is to explore how digital technology can support the process of learning Islam at the secondary education level, particularly in the context of vocational schools. Based on this study, the questions posed are: How is the application of modern technology in teaching Islamic studies at SMK Khozinatul Ulum? What are the challenges and opportunities in integrating technology with traditional knowledge in this context? This study uses a qualitative method with a case study approach. Data were collected through interviews with teachers, classroom observations, and documentation studies related to the use of technology in Islamic learning. The research findings indicate that the integration of digital technology such as the use of online learning applications, social media, and web-based educational platforms has increased student interaction with Islamic materials. However, challenges faced include limited resources and training for educators to utilize technology optimally. This study contributes to designing a more modern and relevant learning approach to the needs of the times.